1997
DOI: 10.1016/s0014-5793(97)00531-0
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer formation of histamine H2 receptors expressed in Sf9 and COS7 cells1

Abstract: A histamine H2 receptor, which had been mutated at its glycosylation site and tagged at its N-terminus with an HA tag (HA-H2 receptor), was expressed in Sf9 cells and COS7 cells. Immunoprecipitation and immunoblotting of HA-H2 receptors with otHA antibody revealed four bands of 31.5 ±2.5 kDa, 59.0 ± 6.0 kDa, 80.5 ± 4.5 kDa and 120 kDa. These bands were also detected by immunoblot using anti-H2 receptor serum (C-terminus). In addition, H2 receptors without the HA-tag coimmunoprecipitated with HA-tagged H2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Currently, we do not know the identity of the multiple bands in Sf9 membranes expressing gpH 1 R, but atypical migration of GPCRs in SDS-PAGE has been repeatedly observed (Grü newald et al, 1996;Kelley et al, 2001;Seifert and Wenzel-Seifert, 2001). Because even complex supramolecular structures such as GPCR dimers are preserved in SDS-PAGE (Fukushima et al, 1997;Hebert and Bouvier, 1998;Kelley et al, 2001), it is possible that the different electrophoretic mobilities of hH 1 R and gpH 1 R reflect different GPCR conformations. The different GPCR conformations may be associated with the specific pharmacological properties of H 1 R species isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we do not know the identity of the multiple bands in Sf9 membranes expressing gpH 1 R, but atypical migration of GPCRs in SDS-PAGE has been repeatedly observed (Grü newald et al, 1996;Kelley et al, 2001;Seifert and Wenzel-Seifert, 2001). Because even complex supramolecular structures such as GPCR dimers are preserved in SDS-PAGE (Fukushima et al, 1997;Hebert and Bouvier, 1998;Kelley et al, 2001), it is possible that the different electrophoretic mobilities of hH 1 R and gpH 1 R reflect different GPCR conformations. The different GPCR conformations may be associated with the specific pharmacological properties of H 1 R species isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…A number of GPCRs have been shown to be capable of forming homodimeric (Hebert et al, 1996;Fukushima et al, 1997;Xie et al, 1999) or heterodimeric (Jordan and Devi, 1999;Marshall et al, 1999;Xie et al, 1999) structures. It has recently been suggested that the dopamine D3 receptor may also form higher order (dimeric and tetrameric) structures (Nimchinsky et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that G-protein-coupled receptors (GPCRs) 1 may form dimers or higher order oligomers (1)(2)(3)(4)(5)(6)(7). This has led to some re-evaluation of the mechanisms thought to be involved in GPCR function.…”
mentioning
confidence: 99%